A survey on pest insect fauna of safflower fields in the Iranian Province of Kohgiloyeh and Boyerahmad - Saeidi, Karim; Adam, Nur Azura (Academic Journals, 2011)
Safflower (Carthamus tinctorius L.) is an important oilseed crop and an essential component of cropping systems in the dry regions and marginal areas of the world. Since the identification of insect pests and their natural enemies is one of the most efficient methods for pest management, an attempt was made to investigate insect fauna in safflower fields of Kohgiloyeh and Boyerahmad Provinces, Iran. To accomplish this, three main cultivation regions were selected and insect pests and their natural enemies were surveyed and collected according to the plant phenology during 2008 to 2009. To sample different techniques, such as sweeping, sticky yellow traps, bait traps and rearing of adult insects, were used. Pest insect fauna was as follows: 1) Pest insects feeding inside the flower heads (bolls) and their natural enemies: Acanthiophilus helianthi, Chaetorellia carthami, Trellia luteola (Tephritidae), Antistrophoplex conthurnatus, Microdontomenu annulatus (Torymidae),Bracon hebetor, Bracon luteator (Braconidae); unidentified specimen (Ichneumonidae), Pronotalia carlinarum(Eulophidae), Ormyrus orientalis (Ormyridae), Colotrechnus viridis, Pteromalus sp. (Pteromalidae), Eurytoma acroptilae (Eurytomidae); Isocolus tinctorius (Cynipidae). 2) Pest insects feeding around the flower heads (bolls) and their natural enemies: Oxycarenus palens, Oxycarenus hyalipennis, Lygus spp. (Lygaeidae), unidentified specimens (Dermestidae), Aphids and Thripses. 3) Pests insects feeding on other parts and their natural enemies: Uroleucon compositae, Pleotrichophorus glandolosus, Brachycaudus helichrysi (Aphididae),Lysiphlebus fabarum (Braconidae), Pachyneuron concolor (Pteromalidae), Coccinella septempunctata,Hippodamia variegata (Coccinellidae), Orius spp. (Anthocoridae); Chrysoperla carnea (Chrysopidae);Neoaliturus fenestratus, Euscelis alsius, Macrosteles laevis, Psammotettix striatus, Circulifer haematoceps(Cicadellidae); Reptalus bitinctus (Cixiidae), Thrips tabaci (Thripidae); Aeolothrips collaris (Aeolothripidae);Haplothrips sp. (Phlaeothripidae), Chromatomyia horticola (Agromyzidae), Agrotis sp., Helicoverpa peltigera(Noctuidae). The results indicate that various insect pests and their natural enemies are active in the safflower fields, and that their identification is very important for various control methods.